Crystal structure and Hirshfeld surface analysis of dimethyl 3-methyl-8-{[4-(trifluoromethyl)phenyl]sulfonyl}-7,8-dihydro-4H-4,6a-epoxybenzo[b]naphtho[1,8-de]azepine-5,6-dicarboxylate - Gleb M. Burkin; Selbi Annadurdyyeva; Alexandra G. Kutasevich; Narmina A. Guliyeva; Khudayar I. Hasanov; Mehmet Akkurt; Gizachew Mulugeta Manahelohe (Acta Crystallographica Section E: Crystallographic Communications)
The molecular conformation of the title compound, C29H22F3NO7S, is stable due to the intramolecular C—H...O hydrogen bonds. The central seven-membered ring adopts a distorted chair form. In the 7-oxabicyclo[2.2.1]hepta-2,5-diene unit, the five-membered rings adopt envelope conformations. In the crystal, the molecules are linked by C—H...O and C—H...F interactions, forming sheets parallel to the (002) plane. Additionally, S—O...π and π–π interactions [centroid-to-centroid distance = 3.6159 (7) Å] connect the molecules along the a-axis direction. van der Waals interactions between the molecular sheets reinforce the molecular packing. A Hirshfeld surface analysis was conducted to visualize the various intermolecular interactions, indicating that the largest contribution to the surface contacts is from H...H interactions (37.3%), followed by O...H/H...O (24.1%), F...H/H...F (19.0%), and C...H/H...C (10.3%) interactions.